Estetika Eksistensi Michel Foucault: Kritik dan Solusi Alternatif atas Radikalisme dan Ekstremisme - Kebung, Konrad (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2018)
This paper presents Foucault’s philosophical thinking on the constitution of the subject as the peak point of all his works from his early writings through his last writings, lectures, and seminars. All his works therefore can be summarized as a technology or a constitution of the self. To Foucault, this particular “self” should be seen as a result of a work of art that is ordered and engraved creatively and continuously. This “self” is seen as a mode of being which is unique, historical and contextual as well. This process Foucault calls an aesthetic of existence. This paper also shows Foucault’s own perspectives on the various radical and extreme movements that often times bring forth a lot of calamities to human life. Using his aesthetic of existence, he tries to look into such problems critically and presents some possible opportunities to minimize or even to erase all kinds of radicalizations and extremisms. Humankind should be able to care of him/her self and therefore he/she should be able to care for others.